SELF-EFFICACY TO VOICE BEHAVIOR: THE ROLE OF CULTURAL INTELLIGENCE AND ORGANIZATIONAL CULTURE - Fridayani, Januari Ayu; Istono, Minta; Kusuma, Stephanus Eri (Fakultas Ekonomi, Universitas Negeri Jakarta, 2024)
The primary objective of this study is to examine the correlation between self-efficacy and voice behavior among student organization members. This investigation holds significant implications for comprehending the intricacies of student organizations within the context of Sanata Dharma University. The present study utilized a sample size of 250 to gather data, and data analysis was conducted with the Partial Least Squares (PLS) Structural Equation Modeling (SEM) technique utilizing the Smart PLS 3 software. The findings of the study indicate that self-efficacy exerted a favorable and statistically significant direct impact on voice behavior. In addition, it is noteworthy to mention another key conclusion, which suggests that cultural intelligence and cultural organization serve as crucial and constructive mediators in the association between self-efficacy and voice behavior. This study offers a comprehensive analysis of the interplay of self-efficacy, cultural intelligence, and cultural organization in influencing the voice behavior of members within student groups. By examining these elements, this research contributes to a more profound comprehension of the underlying dynamics that define these organizations